SAVING INTEREST IN CUSTOMER SATISFACTION MEDIATION, ON CORPORATE CULTURE AND CORPORATE IMAGE ON BMT L-RISMA LAMPUNG TENGAH - Suharto, Suharto (Derivatif : Jurnal Manajemen, 2017)
The purpose of this study is to determine the influence of organizational culture, corporate image in the mediation of customer satisfaction of interest in saving in BMT L-Risma Lampung Tengah. The method used in this research is explanatory survey method. The type of research is quantitative research with the object of organizational culture research, corporate image, customer satisfaction and interest in saving. The research population is BMT L-RISMA customer with the number of samples taken as many as 100 customers. Data collection techniques used interviews, documentation and questionnaires. The analysis tool used is path analysis. The results of the study found that organizational culture, corporate image and customer satisfaction have a direct and positive effect on interest in saving. Organizational culture and corporate image have an indirect effect on interest in saving through customer satisfaction. Looking at these results can be said that all exogenous variables directly positive effect on endogenous variables. Keywords: Organizational Culture, Corporate Image, Customer Satisfaction, Interest of Saving.